Odpowiedź :
[tex]a)\\w(x)=2x(5x^2-x+1)-(-3x^3+x^2+6x-6)=\\\\10x^3-2x^2+2x+3x^3-x^2-6x+6=\\\\13x^3 - 3x^2 - 4x + 6\\\\b)\\w(-\frac{1}{2})=13\cdot(-\frac{1}{2})^3-3\cdot(-\frac{1}{2})^2-4\cdot(-\frac{1}{2})+6=\\\\13\cdot(-\frac{1}{8})-3\cdot \frac{1}{4}+2+6=-\frac{13}{8}-\frac{3}{4}+8=\\\\-\frac{13}{8}-\frac{6}{8}+8=-\frac{19}{8}+8=-2\frac{3}{8}+8=5\frac{5}{8}\\\\\\\\w(\sqrt3)=13\cdot(\sqrt3)^3-3\cdot(\sqrt3)^2-4\cdot \sqrt3+6=\\\\13\cdot 3\sqrt3-3\cdot 3-4\sqrt3+6=39\sqrt3-9-4\sqrt3+6=35\sqrt3-3[/tex]